Republic of Serbia : Financial Sector Assessment Program Update; Technical Note on Corporate and Household Debt Restructuring. (IMF Staff Country Reports; Country Report, 2010)
This Technical Note assesses Corporate and Household Debt Restructuring in Serbia. As of June 2009, nonperforming loans (NPLs) in the banking system constituted 16.5 percent of total loans, owing primarily to the corporate sector. This marks a significant increase over 2008 and, despite a strongly capitalized banking system, underscores a troubling trend. In the current recessionary environment, more businesses are likely to encounter financial distress owing to a decline in demand, shrinking revenues, and untimely payments from their own debtors and customers.